A Qualitative Study of Fertility Preservation Experience in Women with Breast Cancer - Wang Z; Yang X; Hong X; He Y; Xu A; Jiang X; Wei Q (International Journal of Women's Health)
Zilian Wang, Xinyi Yang, Xia Hong, Yu He, Aike Xu, Xuechun Jiang, Qun Wei Reproductive Medicine Center, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Qun Wei, Reproductive Medicine Center, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, No. 3 Qingchun East Road, Hangzhou, Zhejiang, 310020, People’s Republic of China, Email Weiq@srrsh.comObjective: To explore the experiences of women with breast cancer who have undergone fertility preservation and to explore the psychological needs of patients.Methods: Using descriptive phenomenological research methods, 11 patients who underwent oocyte or embryo cryopreservation after diagnosis of breast cancer were selected for semi-structured interviews in a tertiary care hospital. Themes were distilled using Colaizzi’s 7-step analysis and reported according to COREQ guidelines.Results: The experiences of women with breast cancer who underwent fertility preservation can be categorized into 4 themes and 11 sub-themes: a. Physical pain and discomfort (physiological pain, tolerance of physical discomfort); b. heavy psychological burdens (fertility worries, self-blame and guilt, loneliness and helplessness, bias from others and self); c. Actively seeking and benefiting from ways of coping with illness (life over procreation; hope, confidence and courage; positive coping with illness; adequate social support; growth follow in adversity); d. Lack of fertility-related information support.Conclusion: Oncology and reproductive health professionals should pay attention to the experiences of breast cancer patients undergoing fertility preservation and target timely, scientific, and effective interventions to promote disease recovery and improve quality of life.Keywords: breast cancer, tumor, fertility preservation, assisted reproductive technology, qualitative research